Clarion call by an IPS officer - Ali, A. P. Mohammed (Delhi, 2010)
Based on author experience this book help women rights activists and victimologists to broaden their wisdom on the difficulties experienced by the women police, victims/complainants, witnesses and accused while interacting with the women police.
Keywords: Memoirs-IPS